The tadpole of Scinax strigilatus (Spix, 1824) (Anura: Hylidae) - Camurugi, Felipe; Mercês, Ednei De Almeida; Nunes, Ivan; Juncá, Flora Acuña (Zootaxa, 2013)
Scinax strigilatus belongs to the Scinax catharinae species group (sensu Faivovich et al. 2005). It is one of three species [including S. agilis (Cruz & Peixoto) and S. argyreornatus (Miranda-Ribeiro)] of this species group occurring in the Atlantic Forest of the State of Bahia in Brazil (Peixoto & Pimenta 2004; Pimenta et al. 2007; Pimenta & Carvalho-e-Silva 2010). Moreover, the only tadpoles in these three species that have been described are those of S. argyreornatus (Carvalho-e-Silva & Carvalho-e-Silva 1998). We describe herein the tadpole of S. strigilatus.